Dairy manure nitrogen availability in eroded and noneroded soil for sugarbeet followed by small grains - Lentz, Rodrick D; Lehrsch, Gary A; Brown, Bradford; Johnson-Maynard, Jodi; Leytem, April B (Agronomy journal, 2011)
Efficient recycling of abundant manure resources from regional dairy industries in the semiarid West requires a better understanding of N availability in manure-amended soils. We measured net N mineralization using buried bags, and crop biomass, N uptake, and yields for sprinkler-irrigated, whole (noneroded) and eroded Portneuf soils (coarse-silty, mixed, superactive, mesic Durinodic Xeric Haplocalcid) subject to a one-time manure application. Treatments included a control, fertilizer, two rates of composted dairy manure (28.4, 64.3 Mg ha−1, dry wt.), and two rates of stockpiled dairy manure (23.3, 45.7 Mg ha−1, dry wt.) applied in the fall before the Year 1 cropping season. Plots were planted to sugarbeet (Beta vulgaris L.), winter wheat ( Triticum aestivum L.), and spring barley (Hordeum vulgare L.) during the 3-yr study. Overall, net N mineralization rates were low to moderate during winter through spring, decreased in early summer due to N immobilization, then increased to a maximum in late summer, followed by a decrease in fall. The mean mineralization rate (as a percentage of the added organic N) for Years 1, 2, and 3 was −4.2 (N immobilization), 4.3, and 4.8% for compost and 17.4, 17.0, and 11.4% for manure, respectively. Relative to controls, compost and manure treatments as a group increased total 3-yr net N mineralization more for eroded (1.77×) than for whole soils (1.55×). At higher rates, manure also increased immobilization and mineralization in 30- to 60-cm soil depths (below the zone of incorporation). To optimize the use of N mineralized in southern Idaho's manure-amended soils, one should consider the type manure employed and the erosion status of the soil receiving the amendment.